Mapping Australian pharmacy school curricula for content related to pharmacogenomics - Maija-Liisa Venugopal; Faith R. Yong; Natalia Krzyzaniak; Adam La Caze; Christopher Freeman (Elsevier, 2022)
Background: Pharmacogenomics (PGx) is a rapidly growing field which promises to deliver personalized, more effective medications tailored to genetic information. Although the pharmacy profession is expected to lead the translation of pharmacogenomics into widespread clinical implementation, there is a reported lack of preparedness among its members. Assessing pharmacogenomic-related training in Australian pharmacy program curricula may highlight educational gaps and provide guidance for curricula revision. Objective: To examine pharmacogenomic content in Australian tertiary pharmacy program curricula. Methods: We reviewed the curriculum of 22 Australian registrable pharmacy degrees, including 16 Bachelors of Pharmacy programs (with or without honors) and six Masters of Pharmacy programs, for content related to pharmacogenomics and genetics. This was done by screening the publicly available electronic course profiles on each institution's website and searching for key terms such as "pharmacogenomics," "pharmacogenetics," "genes," and "genetics". Three mapping activities were completed to assess the breadth and depth of pharmacogenomic training according to; 1. Bloom's taxonomy, 2. Author-assigned domains comprising; Enabling science, Translational science and Clinical implementation, and 3. Pharmacogenomic competencies from the National Human Genome Research Institute (NHGRI). Results: A total of 18 (82%) pharmacy registrable degree programs incorporated pharmacogenomics and/or genetics in their curricula. Four programs (18%) offered standalone PGx courses and 10 (45%) contained integrated PGx content in other science-related courses (i.e. pharmaceutical biology, biochemistry, microbiology etc.). Mapping activities showed that most learning objectives related to the "Understand" level of Bloom's taxonomy (61%), the "Basic Genetic Concepts" domain of NHGRI's competencies (64%) and "Enabling science" (84%). Conclusions: Most Australian pharmacy registrable degrees have incorporated pharmacogenomic content in their curricula however, the scope of training is limited. Revisions to course curricula should be made to incorporate additional education with a focus on application-based training of clinical pharmacogenomics.